Professional training or competencies for the future? - Yluska Bambirra Assunção; Iris Barbosa Goulart (Future Studies Research Journal: Trends and Strategies, 2016)
The changes in the labor market since the second half of the twentieth century have forced managers to define new ways of selecting and developing employees. In this context, they gained ground discussions on occupational training and competencies identification. This article is a theoretical study, which contributes to the academic conceptual understanding of the constructs professional qualification and competence and stimulates debate and research about which competencies will be most relevant to companies in the future. From the historical analysis and the evolution of these concepts, it becomes clearer the distinction between them, both in French and in American perspective. Interfaces are discussed with the contemporary setting and gives priority to American approach of competence, most widely used model in Brazil. The text aims to identify aspects of competence that address the contemporary setting of the working world and, given the characteristics of the future companies, mentioned in the literature, comments on the convergence of individual competencies (knowledge, skills and attitudes) and meeting future demands labor market.